PROSES TURUN WARIS YANG DITINDAKLANJUTI DENGAN PEMBEBANAN HAK TANGGUNGAN - , JAFAR VENDI HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The reason of taking this topic about âThe Process of Descending Inheritance That Actionable with Installation of Burden Rightâ is there are still many people who do not know that, before selling or encumbering an estate with burden right, there must be done a process of descending inheritance, firstly. So, it would not be done a process of selling or encumbering an inheritance land with burden right which is still named by the person who has passed away. The goal of this fieldwork practice is to fulfill the SKS as the graduation requirement of the author. It also can be a reference in the word of a Notary Public. The benefit that can be earned from this fieldwork practice is getting many knowledge and new experience in the real world of work which has not previously been obtained by the author. The request of descending inheritance is usually submitted by the people for the purpose of switching inheritance of land rights which is owned by the people and originally was on behalf of the person who has passed away become on behalf of the heirs. If an inheritance land would be sold or be installed of mortgage, then it has to pass a process of descending inheritance, firstly. It becomes a legal guarantee of land inheritance which has a valid legal certainty. The request of descending inheritance, essentially, can be done by the respective heirs, so it does not have to go through Notary Public. But, for a process of burden mandatory dependents which go through a Notary Public, because there must be a Mortgage Giving Deed which is made by Notary Public.